2021
DOI: 10.1007/s00170-021-06654-x
|View full text |Cite
|
Sign up to set email alerts
|

WAAM process for metal block structure parts based on mixed heat input

Abstract: Higher penalties may apply, and higher damages may be awarded, for offences and infringements involving the conversion of material into digital or electronic form.Unless otherwise indicated, the views expressed in this thesis are those of the author and do not necessarily Unless otherwise indicated, the views expressed in this thesis are those of the author and do not necessarily represent the views of the University of Wollongong. represent the views of the University of Wollongong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…For example, Xiong et al [17] reported that the parallel contour strategy could cause heat accumulation if the trajectory starts applying an outside-in direction. On the other hand, Cui et al [27] showed better-performed printing using outside-in, considering that the first external bead deposition serves as a limiting wall to guarantee dimensional accuracy. The spiral contour deposition strategy claims, to some extent, to balance the benefits and setbacks of the deposition direction.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Xiong et al [17] reported that the parallel contour strategy could cause heat accumulation if the trajectory starts applying an outside-in direction. On the other hand, Cui et al [27] showed better-performed printing using outside-in, considering that the first external bead deposition serves as a limiting wall to guarantee dimensional accuracy. The spiral contour deposition strategy claims, to some extent, to balance the benefits and setbacks of the deposition direction.…”
Section: Resultsmentioning
confidence: 99%
“…Based on observations, the main factor contributing to the presence of the transition area is the response time of the process, which can be influenced by two factors: machine delay time, and process transition time [21]. The delay time of the wire feeder was measured, and various parameters (including WFS, current, voltage, and others) were recorded during the deposition process.…”
Section: Transition Area Studymentioning
confidence: 99%
“…In the case of WAAM, wide spaces between tracks are necessary due to the width of the beads and their spreading-out character obtained by different welding processes and techniques. For example, Cui et al (2021), depositing a nickel-aluminium-bronze alloy, found layers (with a single pass, or track, deposition per layer) with dimensions ranging from 3.2 to 9.0 mm in width and from 2.6 to 4.5 mm in height, using the gas metal arc welding-cold metal transfer (GMAW-CMT) and GMAW-pulsed processes, respectively. Using carbon steel, Teixeira et al (2022) elaborated a working envelope also with a single deposition pass per layer, covering layer dimensions ranging from 4.8 to 8.1 mm in width and 1.7 to 3.5 mm in height, using GMAW-CMT.…”
Section: Introductionmentioning
confidence: 99%